2011
DOI: 10.1038/leu.2011.328
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of RasGRP1 cooperates with gain-of-function NOTCH1 mutations in T-cell leukemogenesis

Abstract: Ras guanyl nucleotide-releasing proteins (RasGRPs) are activators of Ras. Previous studies have indicated the possible involvement of RasGRP1 and RasGRP4 in leukemogenesis. Here, the predominant role of RasGRP1 in T-cell leukemogenesis is clarified. Notably, increased expression of RasGRP1, but not RasGRP4, was frequently observed in human T-cell malignancies. In a mouse bone marrow transplantation model, RasGRP1 exclusively induced T-cell acute lymphoblastic leukemia/lymphoma (T-ALL) after a shorter latency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
(41 reference statements)
0
27
0
1
Order By: Relevance
“…Previous reports indicate that, as thymocyte maturation progresses, Sos involvement decays and RasGRP1 function becomes prevalent at the level of TCR-mediated signaling (8,14,16,33,34), although a recent study also reported functional cooperation between Sos1 and RasGRP1 during negative thymic selection (17). Consistently, our results showed that the cellular expansion taking place during the transition from DN to DP thymocytes was markedly reduced in Sos1/2 double-null mutants but not in mice lacking only one Sos isoform; such results support the notion of functional redundancy between Sos1 and Sos2 to sustain expansion of thymocytes occurring during progress through these maturation stages.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that, as thymocyte maturation progresses, Sos involvement decays and RasGRP1 function becomes prevalent at the level of TCR-mediated signaling (8,14,16,33,34), although a recent study also reported functional cooperation between Sos1 and RasGRP1 during negative thymic selection (17). Consistently, our results showed that the cellular expansion taking place during the transition from DN to DP thymocytes was markedly reduced in Sos1/2 double-null mutants but not in mice lacking only one Sos isoform; such results support the notion of functional redundancy between Sos1 and Sos2 to sustain expansion of thymocytes occurring during progress through these maturation stages.…”
Section: Discussionmentioning
confidence: 99%
“…RASGRP1-overexpressing T-ALL exhibits constitutively high RAS-GTP, mechanistically distinguishing it from KRAS G12D -driven T-ALL that lacks constitutive GTP loading of RAS. Kitamura and colleagues showed that aberrantly expressed RASGRP1 cooperated with frequent secondary NOTCH1 gain-of-function mutations to promote mouse T-ALL [98]. …”
Section: Contribution Of Wild Type Ras To Ras Wild Type Cancersmentioning
confidence: 99%
“…Insertional mutagenesis in MLV infected mice has been widely used to study lymphoma biology, and several genes, that have since been associated with the development of human lymphomas, including Myc [15], Myb [16], D-type cyclines [17] and RasGrp1 [18] have been identified using these models. In this study, we aimed to identify new genes and pathways deregulated in murine T-LBL by performing integration analysis and gene expression profiling on tumors induced by the SL3-3 MLV.…”
Section: Discussionmentioning
confidence: 99%